The Effects of Patent Characteristics as Signals on the Growth of Follow-on Innovations: Evidence from Chinese Patenting Activities in U.S - GUO, Wenxin (Institutional Knowledge at Singapore Management University, 2009)
As global trade and business activities intensified, cross-national patenting activities have been playing an increasingly important role in the process of innovation accumulation and growth. However, few studies (to my knowledge) have examined the characteristics of cross-national patents and their relationship to the accumulation and growth of innovation, especially in the context of a developing versus a developed country.Motivated by the anecdotal evidence and `Patent Signaling Theory'(Spence, 1973), I investigate the possible influential factors on the `quality' of a US patent with a Chinese priority (thereafter `US-CN' patent) and their impact on the growth of follow-on innovation. By developing and analyzing a unique dataset of 4490 U.S. and Chinese patent matched pair from both U.S. Patent and Trademark Office (USPTO) and State Intellectual Property Office (SIPO), this study investigates the impact of patent strength, patent scope, cross-national inventors, multinational assignees and strength of intellectual property rights (IPR) regime on the growth of innovation in the U.S. The data set consists of patents that are first filed in China, a developing country with uncertain IPR, and subsequently filed and patented in the U.S., a developed country with a mature economy and strong IPR protection.I employ the negative binomial regression model and find that the number of patent claims, patent classes, cross-national inventors and of multinational assignees have a significant and positive impact on the forward citations of the focal patents. I also find that developing a patented innovation under a strong IPR regime does not necessarily increase its follow-on use and innovations as proxied by its forward citations. This work has significant management implications for firm strategies and technology competitiveness especially domestic firms and multinational corporations with activities across national boundaries.